Analysis of the Effect of Dribbling Training on the Technical Performance of Soccer Players: A Systematic Literature Review - Yudha Hafid; Martin Sudarmono (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of dribbling training on the technical abilities of soccer players. This study uses the PRISMA standard in conducting systematic reviews and meta-analyses. The articles reviewed were publications between 2020 and 2024. The search process used the keywords